Improvement of neuronal differentiation by carbon monoxide: Role of pentose phosphate pathway - Almeida, Ana S. (Redox Biol, 2018)
Over the last decades, the silent-killer carbon monoxide (CO) has been shown to also be an endogenous cytoprotective molecule able to inhibit cell death and modulate mitochondrial metabolism. Neuronal metabolism is mostly oxidative and neurons also use glucose for maintaining their anti-oxidant status by generation of reduced glutathione (GSH) via the pentose-phosphate pathway (PPP). It is established that neuronal differentiation depends on reactive oxygen species (ROS) generation and signalling, however there is a lack of information about modulation of the PPP during adult neurogenesis. Thus, the main goal of this study was to unravel the role of CO on cell metabolism during neuronal differentiation, particularly by targeting PPP flux and GSH levels as anti-oxidant system. A human neuroblastoma SH-S5Y5 cell line was used, which differentiates into post-mitotic neurons by treatment with retinoic acid (RA), supplemented or not with CO-releasing molecule-A1 (CORM-A1). SH-SY5Y cell differentiation supplemented with CORM-A1 prompted an increase in neuronal yield production. It did, however, not alter glycolytic metabolism, but increased the PPP. In fact, CORM-A1 treatment stimulated (i) mRNA expression of 6-phosphogluconate dehydrogenase (PGDH) and transketolase (TKT), which are enzymes for oxidative and non-oxidative phases of the PPP, respectively and (ii) protein expression and activity of glucose 6-phosphate dehydrogenase (G6PD) the rate-limiting enzyme of the PPP. Likewise, whenever G6PD was knocked-down CO-induced improvement on neuronal differentiation was reverted, while pharmacological inhibition of GSH synthesis did not change CO's effect on the improvement of neuronal differentiation. Both results indicate the key role of PPP in CO-modulation of neuronal differentiation. Furthermore, at the end of SH-SY5Y neuronal differentiation process, CORM-A1 supplementation increased the ratio of reduced and oxidized glutathione (GSH/GSSG) without alteration of GSH metabolism. These data corroborate with PPP stimulation. In conclusion, CO improves neuronal differentiation of SH-S5Y5 cells by stimulating the PPP and modulating the GSH system.